Reportaż w szkole średniej - Jedliński, Ryszard (Dydaktyka Polonistyczna, 2019)
The article titled Reportage in a high school discusses selected issues related to reading reportage. Working on this type of text aims at understanding features of this genre by students, most of all its structure, composition and narration. Considerations are subordinated to the following aspects: the history of reportage, its definition, functions and structure. The author focuses primarily on literary and journalistic documentary